Immunological correlates of treatment and response in stage IV malignant melanoma patients treated with Ipilimumab - Bjoern, Jon (Oncoimmunology, 2015)
Introduction: Ipilimumab is effective in the treatment of metastatic malignant melanoma, but few biomarkers reliably predict treatment response. Methods: Patients were treated with Ipilimumab for metastatic malignant melanoma. Blood and serum samples were collected before and during treatment. Mononuclear cells in peripheral blood were subjected to immune phenotypic analyses and cytokine levels were measured in serum samples. Results were correlated with clinical data. Results: A total of 40 patients were included in the analyses. Clinical response were associated with an increase after one series of treatment in absolute lymphocyte count (ALC) (p = 0.008), absolute T cell count (p = 0.02) and the absolute number of activated T cells in peripheral blood (p = 0.003). A high frequency of myeloid derived suppressor cells (MDSC) and a higher level of IL6 were associated with treatment failure, though not significantly. Levels of IL6 in serum above the median showed a tendency to associate with reduced survival by the 4th treatment series. Finally, treatment with Ipilimumab led to a decreased frequency of FOXP3+ regulatory T cells (p = 0.009). Conclusion: Ipilimumab leads to increased ALC, T cell count and T cell activation in malignant melanoma patients responding to treatment. A high baseline frequency of myeloid-derived suppressor cells and high levels of IL6 is associated with a reduced chance of responding to therapy.